A systematic review and meta—analysis of the prevalence and associated factors of iron—deficiency anemia among Chinese children under 6 years of age - Li, Weiwei; Gong, Yao; Lai, Yan; Mao, Yu; Wu, Enlian; Feng, Guolian; Yang, Chun; Wang, Jia (Frontiers in Pediatrics, 2025)
BackgroundThis meta-analysis aimed to determine the prevalence of iron-deficiency anemia (IDA) in Chinese children under 6 years of age and identify the associated risk factors.MethodsA comprehensive search was conducted for studies published up to 15 January 2025 in English and Chinese databases (PubMed, Embase, Web of Science, CNKI, and WanFang Data). A random-effects model was used to synthesize prevalence data and risk factors.ResultsTwenty-three studies involving 93,570 children (19,994 with IDA) were included. The overall IDA prevalence was 20.61% (95% CI: 14.68%–26.54%), with higher rates in rural areas (29.96%) compared to urban areas (13.28%). Significant risk factors for IDA included male sex (OR = 1.35), age 6-12 months (OR = 4.10), age 13–24 months (OR = 2.66), low birth weight (<2,500 g) (OR = 1.46), maternal anemia during pregnancy (OR = 2.50), cesarean delivery (OR = 1.18), and premature birth (OR = 2.15). Protective factors included mixed feeding (OR = 0.59), artificial feeding (OR = 0.54), and early introduction of complementary feeding (<6 months) (OR = 0.57). Respiratory diseases, diarrhoea, and formula feeding were not significant risk factors. Meta-regression showed no impact of study design or sample size on these associations.ConclusionRisk factors for IDA in Chinese children under 6 years of age include male sex, younger age (6–24 months), low birth weight, maternal anemia, cesarean delivery, and premature birth. Mixed or artificial feeding and early complementary feeding may protect against IDA. Further large-scale worldwide studies are needed to confirm these findings and inform public health strategies.